Method for producing oxides
Patent Information
- Application Number
- JP2025060577
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2025-04-01
- Publication Date
- 2026-10-14
AI Technical Summary
【0011】 本発明によれば、原料粉末を加熱し600℃から900℃まで上げる時間が5時間未満の焼成工程により1回の焼成で酸化物を合成する。不純物相が合成される化学反応の進行が妨げられるため、立方晶の割合を大きくできる。
Smart Images

Figure 2026167155000001_ABST
Abstract
Description
[Technical Field]
[0001] This invention relates to a method for producing an oxide having a garnet-type crystalline structure containing Li, La, Zr, and Sr. [Background technology]
[0002] Prior art is disclosed in Patent Document 1, which involves calcining a mixture of raw material powders containing Li, La, Zr, and Sr at a temperature of 800-1000°C, pulverizing it, and then calcining it again at a temperature of 1000-1300°C to synthesize an oxide having a garnet-type crystal structure. Oxides having a garnet-type crystal structure exist as cubic or tetragonal crystals, with the cubic crystal exhibiting superior ionic conductivity compared to the tetragonal crystal. [Prior art documents] [Patent Documents]
[0003] [Patent Document 1] Japanese Patent Publication No. 2016-171068 [Overview of the project] [Problems that the invention aims to solve]
[0004] Prior art has the problem that impurity phases such as SrZrO3 are easily formed, which reduces the proportion of cubic crystals.
[0005] This invention was made to solve this problem and aims to provide a method for producing oxides that can increase the proportion of cubic crystals. [Means for solving the problem]
[0006] A first embodiment for achieving this objective is a method for producing an oxide having a garnet-type crystalline structure containing Li, La, Zr, and Sr, comprising a calcination step in which raw material powder is heated to a temperature exceeding 900°C according to a predetermined temperature profile to synthesize the oxide in a single calcination, wherein the time for raising the temperature from 600°C to 900°C is less than 5 hours.
[0007] In the second embodiment, the raw material powder comprises zirconium oxide having a median diameter of 5 μm or less.
[0008] In the third embodiment, in the first or second embodiment, the raw material powder contains lithium carbonate having a median diameter of 50 μm or less.
[0009] The fourth aspect is that, in any of the first to third aspects, the temperature profile is such that the time it takes to raise the temperature from 600°C to 900°C is 3 hours or less.
[0010] The fifth aspect is that, in any of the first to fourth aspects, the oxide further comprises Mg. [Effects of the Invention]
[0011] According to the present invention, oxides are synthesized in a single firing process by heating the raw material powder and raising the temperature from 600°C to 900°C for less than 5 hours. Because the progress of the chemical reaction that synthesizes the impurity phase is hindered, the proportion of cubic crystals can be increased. [Brief explanation of the drawing]
[0012] [Figure 1] This is a schematic diagram of the firing process in one embodiment. [Figure 2] This is a schematic diagram showing the crystal structure of a garnet-type crystal. [Figure 3] (a) is the temperature profile during the firing process, and (b) is another temperature profile. [Modes for carrying out the invention]
[0013] Preferred embodiments of the present invention will be described below with reference to the accompanying drawings. Figure 1 is a schematic diagram of the firing process in one embodiment. The firing process is a process of firing the oxide raw material powder 10 in a furnace (not shown). In this embodiment, the raw material powder 10 is contained in a firing jig 12 (refractory container) placed on the base plate 11 of the furnace.
[0014] Examples of furnaces include a continuous firing furnace in which a base plate 11 moves within a heating zone (not shown) to transport the firing jig 12, and a batch firing furnace in which the base plate 11 is fixed to the furnace and the temperature around the firing jig 12 changes. Examples of continuous firing furnaces include roller hearth kilns, pusher kilns, tunnel kilns, walking beam furnaces, and mesh belt furnaces. In the case of a mesh belt furnace, the base plate 11 may be omitted, and the firing jig 12 may be transported by placing it directly on the mesh belt. The oxide synthesized by firing the raw material powder 10 is a solid electrolyte having a garnet-type crystal structure. The crystal structure of the garnet-type oxide has the general formula C3A2B3O 12 It is represented as follows.
[0015] Figure 2 is a schematic diagram of a garnet-type crystal structure. In the garnet-type crystal structure, the C site Sc is dodecahedral in coordination with the oxygen atom Oa, the A site Sa is octahedral in coordination with the oxygen atom Oa, and the B site Sb is tetrahedral in coordination with the oxygen atom Oa. In the garnet-type crystal structure, Li can be present in the void V, which is the site where the oxygen atom Oa is octahedral in coordination with the oxygen atom Oa. The void V is, for example, the area between B site Sb1 and B site Sb2. The Li present in void V is octahedral in coordination with the oxygen atom Oa that constitutes an octahedron including the tetrahedron face Fb1 forming B site Sb1 and the tetrahedron face Fb2 forming B site Sb2.
[0016] The composition is Li7La3Zr2O 12 In garnet-type oxides, La may occupy the C site (Sc), Zr may occupy the A site (Sa), and Li may occupy the B site (Sb) and the void (V). The skeletal structure of the oxide consists of a LaO8 dodecahedron, a ZrO6 octahedron, and LiO4 tetrahedra sharing vertices or edges. The C site (La site) is substituted with Ca, Sr, Ba, etc., the A site (Zr site) is substituted with Nb, Ta, Sn, Hf, etc., and the B site (Li site) is substituted with Al, Ga, etc. The oxide is substituted with elements according to the CSD (Cambridge Structural Database) X-ray diffraction file No. 422259 (Li7La3Zr2O 12) may differ in diffraction angle and intensity ratio when compared therewith.
[0017] The description will now return to Figure 1. Examples of the raw material powder 10 include mixtures of various metal salts such as oxides, hydroxides, and carbonates containing Li, La, Zr, and Sr. It is possible to use some raw materials in liquid form.
[0018] The raw material powder containing Li is not particularly limited, and examples thereof include lithium carbonate, lithium hydroxide, and lithium nitrate. These may be used singly, or two or more thereof may be combined at any optional ratio. Among these, lithium carbonate, which is easy to handle, is preferable.
[0019] Lithium carbonate preferably has a median diameter of 50 μm or less, more preferably 35 μm or less, in the particle size distribution measured by a laser diffraction / scattering method. Since the metal elements constituting the skeleton structure of the oxide have electronegativities of Li=0.98, La=1.1, and Zr=1.33 (Pauling scale), the LiO4 tetrahedrons and LiO6 hexahedrons have the lowest electronegativity, and strong covalent bonding properties cannot be expected. However, the use of lithium carbonate having a median diameter of 50 μm or less facilitates the formation of LiO4 tetrahedrons and LiO6 hexahedrons, thereby inhibiting the formation of impurity phases such as SrZrO3.
[0020] Examples of the raw material containing La include lanthanum hydroxide and lanthanum oxide. These may be used singly, or two or more thereof may be combined at any optional ratio. Among these, lanthanum hydroxide, which is easy to handle, is preferable.
[0021] Examples of the raw material containing Zr include zirconium oxide and zirconium hydroxide. These may be used singly, or two or more thereof may be combined at any optional ratio. Among these, zirconium oxide, which is easy to handle, is preferable.
[0022] Zirconium oxide is preferably used with a median diameter of 5 μm or less, and more preferably 2 μm or less, as measured by laser diffraction and scattering. Since Zr, which constitutes the oxide's skeletal structure, has high electronegativity, relatively strong covalent bonding is expected in the ZrO6 octahedron. By using zirconium oxide with a median diameter of 5 μm or less, the formation of the ZrO6 octahedron can be further facilitated. This prevents the formation of impurity phases such as SrZrO3.
[0023] Examples of raw materials containing Sr include strontium carbonate, strontium hydroxide, and strontium acetate. These can be used individually or in combination of two or more in any ratio. Among these, strontium carbonate is preferred because it is easy to handle.
[0024] The raw material powder 10 preferably contains Mg. This is because Mg, which substitutes for Li sites, eliminates lattice strain caused by electrostatic repulsion between lithium ions in the crystal lattice, making it easier to establish a cubic crystal system. Examples of raw materials containing Mg include magnesium oxide, magnesium carbonate, and magnesium hydroxide. Among these, magnesium oxide is preferred because it is easy to handle.
[0025] The raw material powder 10 is prepared so that the proportion of metal elements matches or approximates the stoichiometric composition to the extent that the desired oxide can be obtained. The raw material powder 10 may contain certain metal elements that are prone to evaporation and disappearance during calcination, such as lithium, in excess of the stoichiometric composition. Wet mixing and dry mixing can be employed without limitation as means for mixing the powders containing Li, La, Zr, and Sr. Examples of the raw material powder 10 include powder, and molded bodies formed by applying pressure to the powder or agglomerating the powder.
[0026] The method for producing the oxide includes a calcination step of the raw material powder 10. The raw material powder 10 is heated in a calcination jig 12 according to a predetermined temperature profile. The calcination jig 12 includes a bottom 13 and a lid 14. The lid 14 rests on the bottom 13 on which the raw material powder 10 is placed. By covering the bottom 13 with the lid 14 during calcination, the evaporation of lithium contained in the raw material powder 10 and the incorporation of falling materials from the furnace (not shown), such as refractory materials, can be reduced. A hole 15 is provided in the lid 14 that connects the inside of the calcination jig 12 to the outside of the calcination jig 12. The gas generated by the thermal decomposition of the raw material powder 10 escapes to the outside of the calcination jig 12 through the hole 15.
[0027] Examples of materials for the firing jig 12 include inorganic materials such as alumina, cordierite, mullite, silica, magnesia, and zirconia, and metallic materials whose main component is at least one of W, Mo, and Ni. "Main component" means that the combined mass of W, Mo, and Ni is 50 wt% or more of the mass of the metallic material.
[0028] Examples of metallic materials with W as the main component include W, W-Fe alloy, W-ThO2 alloy, W-Mo alloy, W-Zr alloy, W-Ni-Cu alloy, W-Ni-Mo alloy, W-Ni-Fe alloy, W-Ni-Fe-Mo alloy, and W-Ni-Cu-Fe alloy. Examples of metallic materials with Mo as the main component include Mo, Mo-Cu alloy, Mo-Zr-Hf-C alloy, Mo-La2O3 alloy, and Mo-Re alloy. Examples of metallic materials with Ni as the main component include Ni, Ni-Cu alloy, Ni-Mo-Fe alloy, and Ni-Fe alloy.
[0029] Figure 3(a) shows the temperature profile 20 in the firing process. The firing process heats the raw material powder 10 along the temperature profile 20 to a temperature exceeding 900°C, where oxides having a garnet-type crystal structure are synthesized. The temperature of the furnace (not shown) in which the raw material powder 10 is fired is controlled according to the temperature profile 20. The temperature profile 20 involves raising the furnace temperature from room temperature to 100°C at a constant rate, raising the temperature from 100°C to 800°C at a constant rate, raising the temperature from 800°C to 1100°C at a constant rate, maintaining 1100°C for 10 hours, and then lowering the temperature to below 100°C.
[0030] When raw material powder 10 containing Li, La, Zr, and Sr is heated, chemically stable SrZrO3 is readily produced by solid-phase reaction between 600°C and 900°C. When SrZrO3 is produced, there is a shortage of Sr to substitute for the La sites, so the proportion of tetragonal garnet-type oxides increases. To stabilize the cubic system by substituting the Sr contained in SrZrO3 for the La sites, heating to a higher temperature (e.g., 1200°C) increases the amount of Li that evaporates.
[0031] In this embodiment, the temperature profile 20 for heating the raw material powder 10 in the firing process is such that the time 21 for raising the temperature from 600°C to 900°C is less than 5 hours, and the oxide is synthesized in a single firing. A single firing is defined as the time when the temperature of the raw material powder 10 is heated to 400°C or higher and then decreased to 100°C or lower. The raw material powder 10, heated to 400°C or higher, exceeds 900°C once during a single firing, but does not exceed 900°C two or more times. As long as this condition is met, the temperature profile may be stepwise, or the temperature may fluctuate during heating and cooling. This hinders the progress of chemical reactions that synthesize impurity phases such as SrZrO3, thereby increasing the proportion of cubic crystals.
[0032] The temperature profile 20 is more preferably such that the time 21 for raising the temperature from 600°C to 900°C is 3 hours or less. This is because the synthesis of impurity phases is further inhibited, allowing for a further increase in the proportion of cubic crystals.
[0033] Figure 3(b) shows another temperature profile 22. In temperature profile 22, the furnace is heated from room temperature to 100°C at a constant rate, then from 100°C to 800°C at a constant rate, from 800°C to 950°C at a constant rate, maintained at 950°C for 5 hours, then heated from 950°C to 1100°C at a constant rate, maintained at 1100°C for 10 hours, and then cooled to a temperature below 100°C. In temperature profile 22, the time 23 for raising the temperature from 600°C to 900°C is less than 5 hours, preferably 3 hours or less. This is to hinder the progress of the chemical reaction that synthesizes the impurity phase and to increase the proportion of cubic crystals.
[0034] The rate of temperature increase from 600°C to 900°C in the temperature profiles 20 and 22 is an example. The temperature increase rate from 600°C to 900°C is appropriately set such that the times 21 and 23 are less than 5 hours. The minimum value of the times 21 and 23 is set to a time that prevents the firing jig 12 and the furnace from being damaged by thermal shock or the like. The minimum value of the times 21 and 23 is exemplified by 0.1 hour (about 6 minutes).
[0035] The firing can be performed while flowing an atmospheric gas into the furnace. Examples of the atmospheric gas include air-modified gases such as purified gas obtained by removing carbon dioxide from air, inert gases such as argon and helium, neutral gases such as nitrogen and ammonia, and reducing gases such as hydrogen and carbon monoxide.
[0036] The oxide (solid electrolyte) synthesized by firing serves as a material for power storage devices such as secondary batteries and electrochemical capacitors. Examples of the electrochemical capacitor include redox capacitors utilizing redox reactions, and hybrid capacitors which are asymmetric cells combining an electric double layer capacitor and a solid electrolyte. Examples of the material for the power storage device include solid electrolyte (powder), a mixture obtained by compounding a solid electrolyte and an electrolytic solution, and a slurry containing a solid electrolyte and a dispersion medium. [Examples]
[0037] The present invention will be described in more detail with reference to Examples, but the present invention is not limited to these Examples.
[0038] (Example 1) Li 6.95 Mg 0.15 La 2.75 Sr 0.25 Zr 2.0 O 12 The raw material powders Li₂CO₃, MgO, La(OH)₃, SrCO₃, and ZrO₂ were weighed so as to satisfy the composition. In consideration of the volatilization of Li during firing, Li₂CO₃ was added in an excess of about 15 mol% in terms of element. The median diameter of the particle size distribution measured by the laser diffraction / scattering method was 5.9 μm for Li₂CO₃ and 0.9 μm for ZrO₂. The weighed raw material powders were mixed for 0.5 hours with a dry mixer.
[0039] 300g of raw material powder was placed in a mold, and a pressure of 1.6 MPa was applied to the raw material powder using a tabletop press (single-axis molding machine) to obtain a rectangular hexahedron molded body measuring 8cm in length, width, and height, and 4cm in thickness. The molded body was placed in a firing jig, which included a magnesia base, and the molded body (raw material powder) contained in the firing jig was fired in a furnace (batch firing furnace) with nitrogen gas flowing through it.
[0040] The firing temperature profile involved raising the temperature from room temperature to 800°C in approximately 5 hours, then raising it from 800°C to 1100°C in approximately 5 hours, maintaining 1100°C for 10 hours, and finally cooling it down to room temperature. The oxide in Example 1 (hereinafter referred to as "LLZ") was obtained in a single firing cycle by heating the raw material powder according to the temperature profile. The time required to raise the temperature from 600°C to 900°C was 2 hours and 46 minutes.
[0041] (Example 2) The oxide (LLZ) in Example 2 was obtained in the same manner as in Example 1, except that the firing temperature profile was set to raise the temperature from room temperature to 800°C in about 5 hours, then raise the temperature from 800°C to 950°C in about 2 hours, maintain 950°C for 5 hours, then raise the temperature from 950°C to 1100°C in about 2 hours, maintain 1100°C for 10 hours, and then cool down to room temperature.
[0042] (Example 3) The oxide (LLZ) in Example 3 was obtained in the same manner as in Example 1, except that the raw material powder Li2CO3 was replaced with Li2CO3 whose median diameter in the particle size distribution measured by laser diffraction-scattering was 35 μm.
[0043] (Example 4) The oxide (LLZ) in Example 4 was obtained in the same manner as in Example 1, except that the ZrO2 in the raw material powder was replaced with ZrO2 with a median diameter of 2 μm in the particle size distribution measured by laser diffraction-scattering.
[0044] (Example 5) Li 6.95 La 2.75 Sr0.25 Zr 2.0 O 12 The oxide (LLZ) in Example 5 was obtained in the same manner as in Example 1, except that MgO was omitted from the raw material powder.
[0045] (Comparative Example 1) The oxide in Comparative Example 1 was obtained in the same manner as in Example 1, except that the firing temperature profile was set to raise the temperature from room temperature to 650°C in about 3 hours, maintain 650°C for 5 hours, then raise the temperature from 650°C to 800°C in about 1 hour, raise the temperature from 800°C to 1100°C in about 5 hours, maintain 1100°C for 10 hours, and then cool down to room temperature. The time taken to raise the temperature from 600°C to 900°C was 6 hours and 46 minutes.
[0046] (Comparative Example 2) The oxide in Comparative Example 2 was obtained in the same manner as in Example 1, except that the firing temperature profile was set to raise the temperature from room temperature to 800°C in about 5 hours, then raise it from 800°C to 900°C in about 1 hour, maintain 900°C for 5 hours, then raise it from 900°C to 1100°C in about 3 hours, maintain 1100°C for 10 hours, and then cool it down to room temperature. The time taken to raise the temperature from 600°C to 900°C was 6 hours and 46 minutes.
[0047] (Comparative Example 3) The oxide in Comparative Example 3 was obtained in the same manner as in Example 1, except that the firing temperature profile involved raising the temperature from room temperature to 1100°C over approximately 17 hours, maintaining 1100°C for 10 hours, and then cooling down to room temperature. The time required to raise the temperature from 600°C to 900°C was 5 hours.
[0048] (Comparative Example 4) The oxide in Comparative Example 4 was obtained in the same manner as in Example 1, except that the firing temperature profile was set to raise the temperature from room temperature to 800°C in about 5 hours, then raise the temperature from 800°C to 900°C in about 1 hour, maintain 900°C for 10 hours, and then cool down to room temperature (first firing), and then raise the temperature from room temperature to 800°C in about 5 hours, then raise the temperature from 800°C to 1100°C in about 5 hours, maintain 1100°C for 10 hours, and then cool down to room temperature (second firing). The time taken to raise the temperature from 600°C to 900°C was 12 hours and 46 minutes for the first firing and 2 hours and 46 minutes for the second firing (total of 15 hours and 32 minutes for both).
[0049] (Comparative Example 5) The oxide in Comparative Example 5 was obtained in the same manner as in Example 1, except that the Li2CO3 in the raw material powder was replaced with Li2CO3 with a median diameter of 100 μm as measured by laser diffraction-scattering.
[0050] (Comparative Example 6) The oxide in Comparative Example 6 was obtained in the same manner as in Example 1, except that the ZrO2 in the raw material powder was replaced with ZrO2 with a median diameter of 100 μm as measured by laser diffraction-scattering.
[0051] (Powder X-ray diffraction) After grinding the oxide in a glove box under an argon atmosphere using a mortar and pestle, the sample was passed through a sieve with a mesh size of 250 μm to prepare a sample for powder X-ray diffraction. After obtaining the X-ray diffraction pattern of the sample using powder X-ray diffraction with CuKα rays, the X-ray diffraction pattern was analyzed using the Rietveld method to determine the proportion of cubic crystals.
[0052] It is known that the ionic conductivity of LLZ in the cubic crystal structure is higher than that of the tetragonal crystal structure. Since the cubic crystal structure of LLZ is the desired crystal structure and the tetragonal crystal structure is the undesirable crystal structure, samples with a cubic crystal content of 90 mass% (cubic:tetragonal = 90:10) or more were judged as A, samples with a cubic crystal content of 80 mass% or more but less than 90 mass% were judged as B, samples with a cubic crystal content of 70 mass% or more but less than 80 mass% were judged as C, and samples with a cubic crystal content of less than 70 mass% were judged as D. The number of firing cycles, the time taken to raise the temperature from 600°C to 900°C, and the judgments are shown in Table 1.
[0053] [Table 1]
[0054] Examples 1-5, in which the oxide was synthesized in a single firing and the time taken to raise the temperature from 600°C to 900°C was less than 5 hours, received a rating of A or B. However, Comparative Example 1-3, in which the time taken to raise the temperature from 600°C to 900°C was 5 hours or more, received a rating of C, and Comparative Example 4, in which the oxide was synthesized in two firings, received a rating of D. It became clear that the proportion of cubic crystals can be increased by synthesizing the oxide in a single firing with a time taken to raise the temperature from 600°C to 900°C in less than 5 hours. It is presumed that in Examples 1-5, the progress of the chemical reaction that synthesizes SrZrO3 was hindered.
[0055] Comparative Example 5, in which the median diameter of lithium carbonate was 100 μm, and Comparative Example 6, in which the median diameter of zirconium oxide was 100 μm, both received a rating of D. It was confirmed that the median diameter of lithium carbonate and zirconium oxide has a significant impact on the establishment of a cubic crystal system.
[0056] Examples 1 and 2 received a rating of A, while Examples 3-5 received a rating of B. In Example 3, the median diameter of lithium carbonate was 35 μm, in Example 4, the median diameter of zirconium oxide was 2 μm, and in Example 5, the raw material powder did not contain Mg. In Examples 1 and 2, the raw material powder contained Mg, and it is presumed that the proportion of cubic crystals was larger because the median diameters of lithium carbonate and zirconium oxide were smaller compared to Examples 3 and 4.
[0057] Although the present invention has been described above based on embodiments, it can be easily inferred that the present invention is not limited in any way to the above embodiments, and that various improvements and modifications are possible without departing from the spirit of the present invention. The shape and size of the firing jig 12 described in the embodiments are just examples.
[0058] In the examples, we have described a case in which a rectangular hexahedron molded body formed by applying pressure to the raw material powder 10 is fired, but this is not necessarily the only method. It is certainly possible to fire the raw material powder 10 by placing it in a crucible or other container (firing jig). [Explanation of Symbols]
[0059] 10 Raw material powder 20,22 Temperature Profile 21,23 hours
Claims
1. A method for producing an oxide having a garnet-type crystal structure containing Li, La, Zr, and Sr, The process includes a firing step in which the raw material powder is heated to a temperature exceeding 900°C according to a predetermined temperature profile to synthesize the oxide in a single firing, The aforementioned temperature profile is a method for producing oxides in which the time taken to raise the temperature from 600°C to 900°C is less than 5 hours.
2. The method for producing an oxide according to claim 1, wherein the raw material powder comprises zirconium oxide having a median diameter of 5 μm or less.
3. The method for producing an oxide according to claim 1 or 2, wherein the raw material powder comprises lithium carbonate having a median diameter of 50 μm or less.
4. The method for producing an oxide according to claim 1 or 2, wherein the temperature profile is such that the time for raising the temperature from 600°C to 900°C is 3 hours or less.
5. The method for producing the oxide according to claim 1 or 2, further comprising Mg.
Citation Information
Patent Citations
Garnet-type lithium ion conductive oxide
JP2016171068A